Balenciaga's Statement on the Ads Campaign Controversy: Critical Discourse Analysis - Kharismi, Annisa; Nurhayati, Nurhayati (Humanus, 2024)
This study aims to explore and analyze Balenciaga brand statements that are sought to assist in responding after controversy suspected regarding Balenciaga for their choice for adoption of pornography and child exploitation principles. This study applies the qualitative descriptive approach using the theory of critical discourse analysis by Teun A. van Dijk (1993) comprising the dimension of text, social cognition and social context accompanied by Balenciaga’s defensive strategies that emerged from Hood (2011) blame theory. Data were gathered from the social media narrative of Balenciaga official Instagram account. From the results, there were four strategies that Balenciaga employed in using blame-avoiding strategy of image repair which are accepting, downplaying, shifting, and denying.